2016
DOI: 10.2196/jmir.6332
|View full text |Cite
|
Sign up to set email alerts
|

How Professionals Share an E-Care Plan for the Elderly in Primary Care: Evaluating the Use of an E-Communication Tool by Different Combinations of Professionals

Abstract: BackgroundHome-dwelling elderly patients with multimorbidity are at risk of fragmentation of care because of the many different professionals involved and a potentially unclear level of communication. Multidisciplinary communication seems to occur incidentally. Mutual feedback is needed for a professional team to provide consistent care and adequate support to the patient system. eHealth technology can improve outcomes.ObjectiveThe aim of this study was to evaluate the use of a tool, Congredi, for electronic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…CoPs provide a useful model for knowledge management as well as a mechanism that facilitates and promotes a new way of working and learning based on collaborative working and the use of collective intelligence [ 55 ]. They can be especially useful in PC, where flexibility and constant coordination are key aspects of caring for patients with significant multimorbidity [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…CoPs provide a useful model for knowledge management as well as a mechanism that facilitates and promotes a new way of working and learning based on collaborative working and the use of collective intelligence [ 55 ]. They can be especially useful in PC, where flexibility and constant coordination are key aspects of caring for patients with significant multimorbidity [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the telehealth context, the adaptive use of telehealth technology is also expected, as health stakeholders increasingly use multiple technologies to communicate virtually with one another for care management beyond office visits. For example, care providers use personal messaging apps (eg, Whatsapp) and social network sites [11] to moderate communications between patients and care providers in addition to the designated telehealth technologies [7,38]. Hence, care providers’ adequate selection and use of other communication technologies may change the outcomes of telehealth services.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies on information technology use have documented the importance of personal characteristics that help users experiment with and control new technology based on their beliefs and experience. When IT users communicate with others online, in general, and when they act as meeting facilitators in a virtual meeting, in particular, the user who presides over the meeting becomes more important, because individual characteristics such as technology-based skills, capabilities, and level of experience [55] affect the success of online meetings and meeting members’ use of technologies [11,38]. Given that care providers need to facilitate virtual communication with specialists, these users’ characteristics and beliefs about the use of telehealth and relevant technologies simultaneously help to predict the online communication outcome, which is virtual service performance in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings on communication, information, and process mirrored Bardet et al’s meta-model on physician and community pharmacist collaboration [ 36 ]; they identified that early on in a collaboration, key elements include trustworthiness and clarity around roles. Physicians and pharmacists also need to develop an interdependence; establish interest, skills, and positive perceptions; have clear expectations; and build a relationship that is grounded in trust [ 37 , 38 ]. Open and bidirectional communication is also important [ 36 ].…”
Section: Discussionmentioning
confidence: 99%